Analisis Kemampuan Mahasiswa Menyelesaikan Uji Kompetensi Profesional Pendidikan Fisika Uin Alauddin Makassar Pada Mahasiswa Tingkat Akhir Angkatan 2018 - Jusman, Jusman (Al-Khazini, 2022)
This study aims to determine the level of student ability to complete the professional competency test in the Department of Physics Education at UIN Aladdin Makassar for final year students of Class of 2018. The sampling technique used is convenience sampling, namely by taking samples based on students who come to take the competency test. The instrument used in this study is the professional competency test instrument. The type of research used in this study is descriptive quantitative. The results showed that the ability to complete the professional competency test for students of the Department of Physics Education at UIN Alauddin Makassar at the end of the 2018 class was in the low category with an average score of 25.13.